A comparative study of the interactions of cationic hetarenes with quadruplex-DNA forming oligonucleotide sequences of the insulin-linked polymorphic region (ILPR) - Dzubiel, Darinka (Beilstein J Org Chem, 2014)
The interactions of the ILPR sequence (ILPR = "insulin-linked polymorphic region") a2 [d(ACAG(4)TGTG(4)ACAG(4)TGTG(4))] with [2.2.2]heptamethinecyanine derivatives 1a–e and with the already established quadruplex ligands coralyne (2), 3,3′-[2,6-pyridinediylbis(carbonylimino)]bis[1-methylquinolinium] (3), 4,4′,4′′,4′′′-(21H,23H-porphine-5,10,15,20-tetrayl)tetrakis[1-methylpyridinium] (4), naphtho[2,1-b:3,4-b′:6,5-b′′:7,8-b′′′]tetraquinolizinium (5) and thiazole orange (6) were studied. It is demonstrated with absorption, fluorescence and CD spectroscopy that all investigated ligands bind with relatively high affinity to the ILPR-quadruplex DNA a2 (0.2–5.5 × 10(6) M(−1)) and that in most cases the binding parameters of ligand-ILPR complexes are different from the ones observed with other native quadruplex-forming DNA sequences.